Cell death and survival following manual and femtosecond laser-assisted capsulotomy in age-related cataract - Sükösd, Andrea Krisztina (Int J Ophthalmol, 2018)
AIM: To study molecular and morphological changes in lens epithelial cells following femtosecond laser-assisted and manually performed continuous curvilinear capsulotomy (CCC) in order to get information about these methods regarding their potential role in the induction of development of secondary cataract. METHODS: Anterior lens capsules (ALC) were removed from 40 patients with age-related cataract by manual CCC and by femtosecond laser-assisted capsulotomy (FLAC). Samples removed by manual CCC were assorted in group 1, FLAC samples were classified in group 2. Morphology of lens epithelial cells was examined with light and electron microscopes. Following capsulotomy, expressions of p53, Bcl-2 and cyclin D1 genes were analyzed with reverse transcriptase polymerase chain reaction. Immunohistochemistry was used to detect the pro-apoptotic p53 in the epithelial cells. RESULTS: Light and electron microscopic examination showed that ALC of group 1 contained more degenerating cells following manual CCC than after FLAC. The expression level of p53 was higher after manual than laser-assisted surgery. Immunocytochemistry indicated significantly higher number of cells containing p53 protein in the manual CCC group than following FLAC. Bcl-2 and cyclin D1 gene expression levels were slightly lower following manual CCC than after FLAC, but the difference was not significant. CONCLUSION: Manually removed ALC shows slightly, but not significantly larger damage due to the mechanical stretching and pulling of the capsule than those removed using FLAC.